2021
DOI: 10.3389/fnut.2021.785227
|View full text |Cite
|
Sign up to set email alerts
|

Priority Micronutrient Density of Foods for Complementary Feeding of Young Children (6–23 Months) in South and Southeast Asia

Abstract: Background: Given their high nutrient requirements and limited gastric capacity, young children during the complementary feeding period (6–23 months) should be fed nutrient-dense foods. However, complementary feeding diets in low- and middle-income countries are often inadequate in one or more essential micronutrients. In South and Southeast Asia infants' and young children's diets are commonly lacking in iron, zinc, vitamin A, folate, vitamin B12, and calcium, hereafter referred to as priority micronutrients.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…In addition, they could establish nutrition education programs within schools and the public health system and implement social and behavior change communication campaigns through mass media, to sensitize the general population or targeted groups on the importance of regularly consuming these foods within the context of a broader healthy diet. Similar policy and program implications have been identified in a related analysis that focused specifically on young children during the complementary feeding period in South and Southeast Asia and which found that organs, eggs, and bivalves had the highest densities of bioavailable micronutrients commonly lacking (34).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…In addition, they could establish nutrition education programs within schools and the public health system and implement social and behavior change communication campaigns through mass media, to sensitize the general population or targeted groups on the importance of regularly consuming these foods within the context of a broader healthy diet. Similar policy and program implications have been identified in a related analysis that focused specifically on young children during the complementary feeding period in South and Southeast Asia and which found that organs, eggs, and bivalves had the highest densities of bioavailable micronutrients commonly lacking (34).…”
Section: Discussionsupporting
confidence: 63%
“…Finally, plant-source foods generally have lower negative environmental impact than animal-source foods per unit protein, energy, or mass based on current production practices and existing metrics used to quantify environmental impact (40). However, this generalization may not hold when considering the higher bioavailable nutrient density of many animal-source foods as shown in the present analysis and others (34,36), or when considering regenerative production practices and metrics that holistically quantify their environmental impacts (37,38,41).…”
Section: Discussionmentioning
confidence: 84%
“…The NRF6.3 priority nutrients model was based on six nutrients to encourage (calcium, iron, zinc, vitamin A, vitamin B12 and folate) and three nutrients to limit (saturated fat, added sugar and sodium). Although the present scoring NRF6.3 algorithm was very different from that used by Ortenzi and Beal [ 6 ], it was based on the same six priority nutrients [ 6 , 8 ]. The NRF9.3 score was the same as used in many previous studies.…”
Section: Methodsmentioning
confidence: 99%
“…Among the priority micronutrients for LMIC are vitamin A, calcium, iron, zinc, folate, and vitamin B12 [ 6 ]. Past studies of global food composition databases [ 6 , 8 , 9 ] have identified the top food sources of priority micronutrients as organ meats, small fish and shellfish, canned fish with bones, dark green leafy vegetables, eggs, milk, and beef, lamb, mutton, and goat. Cheese, goat milk, and pork were also reported to be good sources of priority micronutrients, and so were fresh fish, yogurt, and dry beans [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation